The Utilization of Instagram as Promotional Media at the Yogyakarta Agricultural Development Polytechnic Library (Jurnal Adabiya, 2025)
This study aims to analyze how Instagram is used as a promotional medium at the Yogyakarta Agricultural Development Polytechnic Library (Polbangtan Yogyakarta). With 89.89 million Instagram users in Indonesia, this platform is considered effective in reaching the wider community. This study uses a qualitative method with a descriptive approach. Data collection was carried out through observation and analysis of the library's Instagram account (@perpuspolbangtanyoma_pertanian) from October to December 2023. The results of the study show that the Yogyakarta Agricultural Development Polytechnic Library uses various Instagram features, such as Feed, Reels, Stories, and Highlights, to promote services, activities, and collections available. Library promotional activities using Instagram as a promotional medium have a positive impact on user engagement, this can be seen from the interaction on uploads and responses to shared content. Instagram has proven to be a useful promotional tool for libraries in attracting user interest in the services offered.ABSTRAK Penelitian ini bertujuan untuk menganalisa bagaimana pemanfaatan instagram sebagai media promosi di Perpustakaan Politeknik Pembangunan Pertanian Yogyakarta (Polbangtan Yogyakarta). Dengan 89,89 juta pengguna instagram di Indonesia, platform ini dianggap efektif dalam menjangkau masyarakat luas. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif. Pengumpulan data dilakukan melalui observasi dan analisis terhadap akun Instagram perpustakaan (@perpuspolbangtanyoma_pertanian) dari Oktober hingga Desember 2023. Hasil penelitian menunjukkan bahwa Perpustakaan Politeknik Pembangunan Pertanian Yogyakarta menggunakan berbagai fitur Instagram, seperti Feed, Reels, Stories, dan Sorotan untuk mempromosikan layanan, kegiatan, serta koleksi yang tersedia. Aktivitas promosi perpustakaan dengan menggunakan Instagram sebagai media promosi berdampak positif pada keterlibatan pemustaka, hal ini terlihat dari interaksi pada unggahan dan respon terhadap konten yang dibagikan. Instagram terbukti menjadi alat promosi yang bermanfaat bagi perpustakaan dalam menarik minat pemustaka terhadap layanan yang ditawarkan.
Keywords: Instagram; Library Promotion; Social Media.